Cardioprotective Regimen of Adaptation to Chronic Hypoxia Diversely Alters Myocardial Gene Expression in SHR and SHR-mtBN Conplastic Rat Strains - Nedvedova, Iveta; Kolar, David; Neckar, Jan; Kalous, Martin; Pravenec, Michal; Šilhavý, Jan; Korenkova, Vlasta; Kolar, Frantisek; Zurmanova, Jitka M. (Frontiers in Endocrinology, 2019)
Adaptation to continuous normobaric hypoxia (CNH) protects the heart against acute ischemia/reperfusion injury. Recently, we have demonstrated the infarct size-limiting effect of CNH also in hearts of spontaneously hypertensive rats (SHR) and in conplastic SHR-mtBN strain characterized by the selective replacement of the mitochondrial genome of SHR with that of more ischemia-resistant Brown Norway rats. Importantly, cardioprotective effect of CNH was more pronounced in SHR-mtBN than in SHR. Thus, here we aimed to identify candidate genes which may contribute to this difference between the strains. Rats were adapted to CNH (FiO2 0.1) for 3 weeks or kept at room air as normoxic controls. Screening of 45 transcripts was performed in left ventricles using Biomark Chip. Significant differences between the groups were analyzed by univariate analysis (ANOVA) and the genes contributing to the differences between the strains unmasked by CNH were identified by multivariate analyses (PCA, SOM). ANOVA with Bonferroni correction revealed that transcripts differently affected by CNH in SHR and SHR-mtBN belong predominantly to lipid metabolism and antioxidant defence. PCA divided four experimental groups into two main clusters corresponding to chronically hypoxic and normoxic groups, and differences between the strains were more pronounced after CNH. Subsequently, the following 14 candidate transcripts were selected by PCA, and confirmed by SOM analyses, that can contribute to the strain differences in cardioprotective phenotype afforded by CNH: Alkaline ceramidase 2 (Acer2), Fatty acid translocase (Cd36), Aconitase 1 (Aco1), Peroxisome proliferator activated receptor gamma (Pparg), Hemoxygenase 2 (Hmox2), Phospholipase A2 group IIA (Ppla2g2a), Dynamin-related protein (Drp), Protein kinase C epsilon (Pkce) Hexokinase 2 (Hk2), Sphingomyelin synthase 2 (Sgms2), Caspase 3 (Casp3), Mitofussin 1 (Mfn1), Phospholipase A2 group V (Pla2g5) and Catalase (Cat). Our data suggests that the stronger cardioprotective phenotype of conplastic SHR-mtBN strain afforded by CNH is associated with either preventing the drop or increasing the expression of transcripts related to energy metabolism, antioxidant response and mitochondrial dynamics.